Development Of An Improved Algorithm Of Mppt Technique For Photovoltaic Power Generation - Hariri, Muhammad Hafeez Mohamed (2013)
This thesis presents a simple control technique which was used in Maximum Power Point Tracking (MPPT). A new algorithm for battery charging, overcharge protection and maximum power tracking in Perturbation and Observation (P&O) technique was implemented. The improvement of the control technique had achieved an optimal efficiency for the stand-alone PV system. The application of improved P&O in synchronous DC-DC buck converter for battery charging application had optimize the maximum available power for PV module. The synchronous DC-DC buck design achieved 80% efficiency. It is found that with an improved P&O MPPT algorithm had increased maximum PV output power by 13% when compared to a PV system without MPPT implementation.